Homoclinic solutions for fractional discrete Laplacian equations. (September 2020) - Xiang, Mingqi; Zhang, Binlin
Abstract: In this paper, we introduce a variational framework to a fractional difference equation on Z driven by the fractional discrete Laplacian and involving a coercive weight function and a positive parameter λ . By means of the critical point theory, we prove the existence of at least two nontrivial and nonnegative homoclinic solutions for λ big enough.